Early Sport Specialization Trends and Injuries in Former High School Athletes Specialized in Sports - Nagano Y; Oyama T (Dove Medical Press, 2023)
Yasuharu Nagano,1 Takashi Oyama2 1Department of Sports and Health Science, Japan Women's College of Physical Education, Tokyo, Japan; 2Faculty of Economics, Teikyo University, Tokyo, JapanCorrespondence: Yasuharu Nagano, Department of Sports and Health Science, Japan Women's College of Physical Education, 8-19-1, Kitakarasuyama, Setagaya, Tokyo, 157-8565, Japan, Tel/Fax +81-3-3300-5437, Email nagano.yasuharu@jwcpe.ac.jpPurpose: Determining the effects of early specialization in a specific sport is difficult. Therefore, it is necessary to investigate its effects based on the type of sports. The purpose of this study was to investigate the proportion of participants who had been participating in a single sport, in individual or team sports from an early age and to compared the prevalence of acute and overuse injuries among these participants.Methods: A total of 1377 adult participants (team sports = 700, individual sports = 637) retrospectively completed a questionnaire assessing sports participation from elementary school to high school and injury history (acute and overuse) at high school age. The proportions of the specialized / nonspecialized groups per sport type were compared, and differences in acute or overuse injury prevalence were examined.Results: The proportion of the specialized group participants who continued to play the same single sport from elementary school age to high school age was greater in team sports (33.6%) than that in individual sports (19.2%) (p < 0.01). The specialized group participating in team sports had a greater prevalence of overuse injury at high school age than the nonspecialized group (p < 0.05) who previously participated in several sports. However, the prevalence of overuse injury at high school did not significantly differ between the specialized and nonspecialized groups participating in individual sports.Conclusion: More children who continued to play only one sport from elementary school age to high school age played in team sports in Japan. They also had a higher prevalence of overuse injuries when they were at high school age. It is necessary to consider the environment to play multi sports before high school age, especially in team sports.Keywords: children, injury and prevention, musculoskeletal, youth, history